Identifikasi Hambatan Belajar Mahasiswa Universitas Sriwijaya Pada Masa Pandemi Covid-19 - Rani Mega Putri; Rahmi Sofah; Silvia AR; Ilham Arvan Junaidi (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This study aims to identify learning barriers of Sriwijaya University students during the Covid-19 pandemic. The method used in this research was a survey. The subjects in this study were students of the Guidance and Counseling Study Program, Sriwijaya University. The data collection technique used a questionnaire instrument that was distributed to respondents online using a google form. The results of the study showed that the learning barriers of Sriwijaya University students on internal factors amounted to 56.58%, while on external factors amounted to 55.12%.  So, it can be concluded that the two factors of learning barriers are in the medium category.